2022
DOI: 10.3389/fmed.2022.810907
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Nomogram in Lung Cancer With Obstructive Sleep Apnea Syndrome

Abstract: To analyze the prognostic factors and survival rate of lung cancer patients with obstructive sleep apnea (OSA) by nomogram. The nomogram was established by a development cohort (n = 90), and the validation cohort included 38 patients. Factors in the nomogram were identified by Cox hazard analysis. We tested the accuracy of the nomograms by discrimination and calibration, and plotted decision curves to assess the benefits of nomogram-assisted decisions. There were significant difference in sex, apnea hypopnea i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Liu et al. retrospectively analyzed the data of 410 patients with newly diagnosed lung cancer, and a total of 128 patients (31.2%) had OSA, a slightly lower prevalence compared to that reported by other studies ( 21 ).…”
Section: Epidemiologymentioning
confidence: 88%
See 1 more Smart Citation
“…Liu et al. retrospectively analyzed the data of 410 patients with newly diagnosed lung cancer, and a total of 128 patients (31.2%) had OSA, a slightly lower prevalence compared to that reported by other studies ( 21 ).…”
Section: Epidemiologymentioning
confidence: 88%
“…Another clinical cohort study from Asia confirmed that the prevalence of OSA in patients with lung cancer was 57%, with moderate-severe OSA accounting for 27% of the total, especially in patients with SCLC, an elevated AHI, and oxygen desaturation index (ODI), indicating that hypoxia may be more severe (20). Liu et al retrospectively analyzed the data of 410 patients with newly diagnosed lung cancer, and a total of 128 patients (31.2%) had OSA, a slightly lower prevalence compared to that reported by other studies (21).…”
Section: Osa In Patients With Lung Cancermentioning
confidence: 88%
“…Additionally, elevated MPV values can aid in identifying high-risk individuals with OSAHS and alert clinicians to the potential increased risk of CVDs. OSAHS is a chronic condition that can lead to various comorbidities, including respiratory diseases, endocrine dysfunction, and cognitive impairment [61][62][63]. CVDs are a prominent comorbidity of OSAHS, especially coronary artery disease [64].…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea-hypopnea syndrome (OSAHS) is a sleep-related breathing disorder characterized by snoring and the repetitive collapse of the upper airways, which disrupts normal ventilation [ 1 , 2 ]. OSAHS is associated with multiple comorbidities, including cardiovascular events and chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%